(untitled) (Medico Legal Update, 2021)
This study was conducted to assess the role of apigenin extracted from parsley seeds either in glycosidic (aqueous extract) or aglycone forms (organic solvent extract), comparing to butylated hydroxyl tolouene (BHT)in serum lipid profile and brain tissue peroxidation in H2O2 induced oxidative stress adult male rats. The yield of crude flavonoids from parsley seeds was found to be approximately 2.65% and thin layer chromatography techniques confirmed that apigenin is the main flavonoid with RF similar to that of the standard apigenin. Experimentally induction of oxidative stress in male rats by 0.75% H2O2 in drinking water for eight weeks showed a significant alterations in normal serum lipid profile manifested by significant elevation (p<0.05) in total cholesterol, Triacyle glycerol (TAG), Low density lipoprotein-Cholestrol (LDL-C) and Very low density lipoprotein-Cholestrol (VLDL-C) and a significant decrease in High density lipoprotein-Cholestrol (HDL-C) as compared to the control and BHT treated groups. On the other hand, daily oral administration of apigenin in a dose of 150 mg/Kg B.W. to H2O2 treated groups were caused a significant correction of the lipid profile parameters. Examination of brain tissues of H2O2 and apigenin concurrent H2O2 treated rats showed a significant decrease (p<0.05) in brain tissue malondialdehyde (MDA) and significant elevation in catalase and cholinesterase activities in apigenin and BHT treated groups comparing with H2O2 treated and control groups.